CERITA RAKYAT INDRAGIRI SEBAGAI BAHAN PENGAJARAN SASTRA DI SEKOLAH DASAR DALAM UPAYA PEMBENTUKAN KARAKTER ANAK - Marlina, NFN (SUAR BETANG, 2017)
This study discusses three Indragiri folklores as literary teaching materials in elementary school in the effort to build students character. The purpose of this study is to introduce culture and oral tradition through literature in order to build the character of children. The type of this research is descriptive analysis. The three folktales are described and the good characters contained in the story that can be imitated and emulated by children is analyzed. The data were analyzed by applying moral approach. The result shows that the three Indragiri folklores contain good characters that can be imitated and emulated by children. Therefore, base on this study, it can be concluded  that folklore can be used as a teaching material for literary learning at the elementary level in order to build children’s character